Celiac disease - a common autoimmune disease with significantly delayed diagnosis - Choina, Magdalena; Kinga Pożarowska; Rudziński, Gracjan; Cukrowska, Bożena; Majsiak, Emilia (Journal of Education, Health and Sport, 2022)
Introduction: Celiac disease (CD) is an autoimmune disease that affects genetically predisposed individuals. In course of the disease, consumption of gluten causes damage to the small intestine. Due to various clinical manifestations, diagnosing CD poses a challenge to clinicians. It has been proven by several study groups that the diagnostic delay in CD is still too long and provokes severe health complications. Purpose: The aim of the study is to highlight the importance of diagnostic delay in CD, its consequences and possible solutions. Description of the state of knowledge: The diagnosis of CD is based on the clinical picture, serological test, duodenal mucosal biopsies and genetic tests. Many cases of CD remain undiagnosed in spite of published guidelines for CD diagnosis. Consequently, the diagnosis is significantly delayed: the mean duration of the diagnostic process in Poland was 7.3 years. In other countries, patients the time from the onset of the symptoms to establishing CD diagnosis was up to 10 years. The diagnostic delay leads to reduced quality of life and the development of severe complications, such as neoplastic disease. Summary: Diagnostic delay in CD is an issue of great importance. Because of the reduced quality of life and the possibility of neoplasm, it is crucial to take action in order to shorten the diagnostic process of CD.